Intership program: A viewpoint of pre-service teachers of Farhangian University-Shahid Beheshti branch of Tehran - Sharafie, Darioush; Ghorbani, Mohamadreza; Dadashzadeh, Amin (University of Muhammadiyah Malang, 2019)
The internship has been considered as a crucial program in preparing pre-service teachers to implement the scientific-practical activities knowledge they have gained. This study aimed at describing the implementation as well as the function of the internship program based on pre-service teachers' of Farhangian University-Shahid Beheshti branch of Tehran viewpoint. The statistical population of this study was the student teachers of Shahid Beheshti Higher Education Center entering the year 2015 in which the 119 people of them were selected as the sample. As many as 31 questions about six main criteria (the assessment of Farhangian University, internship course lecturers, schools where the interns went for internship, teachers who guided interns in schools, self-assessment of internships and the assessment of education department) were designed and verified by internship professors and then a five-choice questionnaire was designed based on Likert Scale. The data obtained then analyzed using single sample t-test. The results obtained from the questionnaire proved that the university, internship lecturers and guidance teachers did not succeed in fulfilling their tasks. Thus, good coordination among university, Department of Education, and schools should be established.